O relacionamento entre as instituições de ensino superior e seus ex-alunos: reflexos na capacitação de recursos - Estudo de Caso da Escola de Administração de Empresas de São Paulo da Fundação Getulio Vargas e do Instituto Presbiteriano Mackenzie - Adam, Márcia Cristina Pastore (2007)
The proposal of the present work is the presentation of a case study of fund raising with alumni from two Brazilian Higher Education Institutions, the FGV-EAESP and the Mackenzie; analyzed through the lens of relationship marketing. The referenced presentation resulted from the practical experience of these two institutions, making it possible to prove the importance of the relationship of these institutions to their alumni, representing much more than a source of sustainability. It signifies the continuity of the institutions, since the main purpose of the relationship is to keep strong the bonds of the alumni with their alma mater. For that, interviews with the leaders and fundraisers of the two institutions have been performed, with the intention to elucidate how the fundraising process with the alumni started, the techniques of making solicitations, and the results. The problem of the research follows from the question: how can relationship marketing contribute to fundraising with alumni of these institutions? Starting from the analysis of the fund raising developed by the two institutions with their alumni, it arrives at the central point of work, which is the analysis of the influence and the interposition of the relationship in relation to the results obtained from the fund raising. The approach of Relationship Marketing is appropriated to fund raising in non profit institutions and its relevance is essential in this research to understand the cases described and explain the successes realized. It is concluded that the tools of relationship marketing have been partially applied in the two institutions and resulted in success in fund raising, as can be confirmed in the respective financial results. The most important aspect is the commitment to keeping the relationship, by means of communication, information technology, and involvement. However, the alternation of power in the governing body of both institutions interrupts the leadership of fund raising, a fundamental factor for the success of this type of action with alumni. Without the maintenance and the continuity of the relationship with the alumni, the fund raising sector loses position in strategic planning, becoming weakened or completely abandoned